Prevalence of Delirium and Its Clinical Outcome in Adult Filipino Patients Admitted in The Intensive Care Unit - Abram P Tanuatmadja; Jacqueline R Vea (Journal of Medicine and Health, 2019)
Delirium is common in the ICU setting and is associated with increased morbidity, manpower requirement, and costs. This study aims to investigate the prevalence of delirium and its outcome in terms of 14-days mortality and length of ICU stay in ICU patients. The study was done at a 150-bed tertiary teaching hospital, located in Quezon City, Metro Manila, February to September 2016. This is a prospective studyinvolving 136 adults. Screening for delirium was done within 24 hours of ICU admission using both CAM-ICU scoring method and DSM-IV-TR criteria for delirium. Delirium prevalence was found to be 5.15%. The average age was higher in the subjects positive for delirium (70.14 + 21.15 years versus 60.43 + 16.10 years, p=0.1286). At the time of ICU admission, 11.54% of sedated patients were positive for delirium compared to 3.64% of non-sedated patients, p=0.1513 ;OR 3.457. Delirium was associated with higher 14 days mortality (OR 16.8, p=0.0212). Subjects positive for delirium had 2.74 longer days average ICU stay compared to the other group, with p=0.026. We concluded delirium was associated with higher 14-days mortality and longer ICU stay. Keywords : delirium, prevalence, Intensive Care Unit